Prapemrosesan untuk Klasifikasi Gambar Aksara OKU Timur - Prasetya, M. Iqbal; Yadi, Ilman Zuhri; Kunang, Yesi Novaria; Permatasari, Susan Dian (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study investigates methods to enhance the quality of OKU Timur script images through preprocessing techniques utilizing Adaptive Thresholding. The OKU Timur script, significant for daily communication and traditional ceremonies, encounters challenges such as skew, rotation, and low resolution in image processing. The proposed preprocessing approach includes contrast normalization to improve image clarity, noise reduction to eliminate unwanted artifacts, and feature extraction to emphasize critical image characteristics. These steps are designed to enhance the accuracy of character recognition. The findings indicate that proper preprocessing is crucial for effective recognition of OKU Timur script and holds substantial potential for preserving this cultural heritage through modern technological applications.